Neoliberalism and the Demeaning of Student Movements - Ferguson, Roderick A (We Demand, 2017)
The “educational danger” of student movements—to reformulate Howard Zinn’s phrase¹—lies in their capacity to produce insurgencies, insurgencies that are created by connecting social formations and processes that are supposed to be understood as disparate. We may understand student movements as efforts to illustrate the connections among systems of power that arose between academy, government, and corporation. The previous chapter used the increasing visibility of minoritized communities to explain the social ruptures that student and social movements produced in the 1950s, ’60s, and ’70s; this chapter looks at how systems of power have responded to those movements by demeaning